'It's a Good Job Nobody Mentioned Hedgehogs': The Use of Narratives in Discworld Fandom. Issue 1 (2nd January 2017) - Löfgren, Jakob
Abstract: This article examines the use of staged narratives in the Hogswatch celebration—a celebration of Terry Pratchett's fictional Discworld held in November in Wincanton, Somerset. Different narratives are used in fandom as part of the process of qualia resituation, in which the what-it-is-like of the Discworld series is conveyed in the fandom celebration.